Pan Africanism, Regional Integration and Development in Africa
XXI, 326 p. 3 illus.
Keywords: This edited volume addresses the accomplishments, prospects and challenges of regional integration processes on the African continent. Since regional integration is a process that ebbs and flows according to a wide range of variables such as changing political and economic conditions, implications and factors derived from the vagaries of migration and climate change, it is crucial to be cognizant with how these variables impact regional integration initiatives. The contributors discuss the debates on Pan-Africanism and linking it with ongoing discourses and policies on regional integration in Africa. Other aspects of the book contain some of the most important topic issues such as migration, border management and the sustainable development goals. This content offers readers fresh and innovative perspectives on various aspects of sustainable development and regional growth in Africa.